Efektivitas Ketinggian Perangkap Lalat Buah Pada Jeruk Siam Banjar pada Sistem Surjan - Riswandha Imam; Noor Laili Aziza; Hairu Suparto (Agroekotek View, 2021)
The Banjar siam orange is a type of citrus that is widely cultivated with the Surjan system in South Kalimantan, especially in the Barito Kuala area. However, the productivity of this fruit is still below standard due to the attack of fruit flies. This study aims to determine the effect of the application of fruit fly traps with different heights on the population of siam Banjar citrus fruit flies that are trapped and to determine the height of the siam Banjar orange fruit fly trap which is the most effective for controlling fruit fly pests. This research was conducted in the land of Banjar oranges in Simpang Nungki Village Cerbon Barito Kuala Regency for two months, from July to September 2020 using the one-factor randomized block design (RAK) method consisting of five treatments. These factors are the various kinds of heights and the five treatments are 0 m from the top of the plant (P1), 0.5 m from the shoot (P2), 1 m from the top of the plant (P3), 1.5 m from the top of the plant (P4), 2 m from the top of plant (P5). The treatment was repeated five times so that there were 25 experimental units. The results showed that the application of fruit fly traps with different heights had no significant effect on the population of siam Banjar citrus fruit flies in each trap. The height of the application of the siam Banjar orange fruit fly trap that traps the most fruit flies is the treatment of hanging fruit fly traps at an altitude of 1 m from the tops of citrus plants.